(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
This research was based on the technical and productive characterization of the dairy cattle system in the Bolívar canton (latitude: -0.841025 longitude: -80.1667) of the province of Manabí, in order to gather information on its current status. For this, the total number of active members of ASOGABO (Cattlemen’s Association of Canton Bolivar) was known and the sample was calculated (10 members), then a questionnaire was designed, a card (applied during 7 days at milking time) and a MAGAP checklist was used as a reference. Using these tools, it was found that, in most of the farms, the amount of milk obtained is low in relation to the Sierra region, and it was also established that farm, genetic group and lactation time have a statistical influence on milk production. In addition, it was determined that none of the farms complied with the requirements established by good livestock practices for milk production, and three aspects were identified as the main problems (infrastructure, feeding and milking management).